Silicon-carbon negative electrode material and preparation method and application thereof
By using silicon iodide steam to deposit nanosilicon in porous carbon in lithium-ion batteries, a silicon carbon negative electrode material with high specific capacity and first-time efficiency was prepared, which solved the problem of charging volume expansion of silicon material, reduced production costs and safety risks, and promoted the industrialization of materials.
Patent Information
- Application Number
- CN202411646063.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
The existing silicon materials in lithium-ion batteries have ruptured and powdered particles due to expansion of charging volume, which consumes a large amount of active lithium, reduces the battery capacity, and the use of silane vapor deposition poses safety risks and high costs, which limits the industrialization of silicon-carbon materials.
Nanosilicon is pyrolyzed and deposited in porous carbon by using silicon iodide steam, and prepared silicon carbon negative electrode material through passivation treatment. The specific pore size distribution of porous carbon is used to promote the uniform deposition of silicon iodide and reduce the charging volume expansion effect.
It improves the energy density and first charge and discharge efficiency of lithium-ion secondary batteries, reduces production costs and safety risks, is suitable for large-scale production, and promotes the industrialization of silicon-carbon negative electrode materials.
Smart Images

Figure CN119503770A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] With the development of new energy electric vehicles and electric aircraft, the market demand for high energy density electrode materials is becoming more and more urgent. At present, the capacity of mainstream graphite negative electrode materials is only 340mA·h / g-360mA·h / g, which is close to the theoretical capacity. Among many negative electrode materials, silicon materials have the highest theoretical lithium storage capacity and form Li 15 Si 4 The theoretical capacity can reach 3579mA·h / g. Using silicon materials in the negative electrode of the battery can greatly improve the energy density of the battery.
[0003] However, silicon materials have high capacity and are accompanied by huge charging volume expansion. Excessive volume expansion can easily lead to particle breakage and pulverization, consume a large amount of active lithium, and ultimately cause the negative electrode and battery capacity to decay rapidly. At present, this problem is mainly solved by reducing the size of silicon through silane vapor deposition in porous carbon. Although the vapor-deposited silicon carbon obtained in this way has good performance, silane is flammable and explosive and expensive, which greatly hinders the industrialization of deposited silicon carbon.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One of the purposes of the present invention is to provide a method for preparing a silicon-carbon negative electrode material, which is not only simple and safe, suitable for industrial mass production, but also can effectively improve the initial efficiency and specific capacity of the negative electrode material, and can safely and low-cost mass produce silicon-carbon negative electrode materials with good performance.
[0006] The second object of the present invention is to provide a silicon-carbon negative electrode material having a higher specific capacity and initial efficiency and a lower charging volume expansion effect, which is beneficial to improving the energy density of lithium-ion secondary batteries and improving the initial charge and discharge efficiency.
[0007] The third object of the present invention is to provide an application of a silicon-carbon negative electrode material, which can effectively improve the energy density of lithium-ion secondary batteries and effectively improve the initial charge and discharge efficiency, and has outstanding application effects.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] In a first aspect, a method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0010] The silicon iodide vapor is pyrolyzed in the porous carbon to deposit nano-silicon in the pore structure of the porous carbon to obtain a silicon-carbon precursor, and the silicon-carbon precursor is passivated to obtain the silicon-carbon negative electrode material;
[0011] The pore volume of the porous carbon is 0.6 cm 3 / g~1.4cm 3 / g between;
[0012] The pore structure of the porous carbon includes pores with a diameter of 0.5 nm to 3 nm, pores with a diameter of 3 nm to 8 nm, and pores with a diameter of 8 nm to 80 nm.
[0013] Furthermore, the volume proportion of pores with a diameter of 0.5 nm to 3 nm in the porous carbon is 55% to 75%;
[0014] Preferably, the volume proportion of pores with a diameter of 3 nm to 8 nm in the porous carbon is 10% to 20%;
[0015] Preferably, the volume proportion of pores with a diameter of 8 nm to 80 nm in the porous carbon is 15% to 25%.
[0016] Furthermore, the median particle size D50 of the porous carbon is 1 μm to 9 μm;
[0017] Preferably, the specific surface area of the porous carbon is 500 m 2 / g~3000m 2 / g.
[0018] Furthermore, the method for preparing the porous carbon comprises the following steps:
[0019] (a) pre-carbonizing a carbon source material to obtain a pre-carbonized product;
[0020] (b) the pre-carbonized product is sequentially subjected to carbonization, pulverization and activation treatment to obtain the porous carbon;
[0021] Preferably, the carbon source material comprises at least one of glucose, fructose, galactose, lactose, sucrose, maltose, rice starch, mung bean starch, wheat starch, cassava starch, corn starch, cellulose and phenolic resin;
[0022] Preferably, the pre-carbonization method includes at least one of solvent thermal reaction, low temperature carbonization and spray drying;
[0023] Preferably, the activation treatment includes at least one of a physical activation method and a chemical activation method;
[0024] Preferably, the gas used in the physical activation method includes at least one of water vapor, air and carbon dioxide;
[0025] Preferably, the chemical reagent used in the chemical activation method includes at least one of phosphoric acid, zinc chloride, potassium hydroxide and sodium hydroxide.
[0026] Furthermore, the method for preparing silicon iodide vapor comprises the following steps:
[0027] Iodine vapor is introduced into silicon particles for reaction to obtain silicon iodide vapor;
[0028] Preferably, the silicon particles include at least one of metallic silicon, high-purity silicon and ultra-pure silicon;
[0029] Preferably, the particle size of the silicon particles is between 0.1 mm and 500 mm.
[0030] In a second aspect, a silicon-carbon negative electrode material is prepared by any of the preparation methods described above.
[0031] Furthermore, the general structural formula of the silicon-carbon negative electrode material is Si / C m , where 0.25≤m≤4;
[0032] Preferably, the mass content of iodine in the silicon-carbon negative electrode material is 0.01% to 0.20%;
[0033] Preferably, the median particle size D50 of the silicon-carbon negative electrode material is 2 μm to 10 μm;
[0034] Preferably, the specific surface area of the silicon-carbon negative electrode material is 0.5 m 2 / g~15m 2 / g.
[0035] Furthermore, the nano-silicon content in the silicon-carbon negative electrode material is 20wt% to 80wt%;
[0036] The nano silicon is amorphous silicon;
[0037] Preferably, the average particle size D50 of the nano-silicon is less than 20 nm.
[0038] A third aspect is an application of the silicon-carbon negative electrode material described in any one of the above items in a lithium-ion secondary battery.
[0039] Furthermore, when the battery is discharged at a constant current to 0.005 V and then charged at a constant current to a voltage of 1.5 V, the negative electrode capacity of the lithium ion secondary battery is ≥1800 mA·h / g, and the initial efficiency is ≥90%.
[0040] Compared with the prior art, the present invention has at least the following beneficial effects:
[0041] The preparation method of silicon-carbon negative electrode material provided by the present invention adopts silicon iodide vapor as silicon source gas to deposit nano-silicon. Compared with the prior art which uses silane gas, which results in higher production cost and greater safety risk, and seriously limits the stable batch production of silicon-carbon negative electrode materials, silicon iodide has a stable structure, does not catch fire when leaked, is not flammable or explosive, can greatly improve the stability and safety of production, and can promote the industrialization progress of vapor-phase deposited silicon-carbon; in addition, iodine vapor decomposed by silicon iodide can be recycled, which can significantly reduce production costs; since silane molecules are small, they will cause faster diffusion, decomposition and deposition speeds, This results in a larger particle size of nano-silicon, while silicon iodide can effectively avoid the above problems due to its large molecule; at the same time, because the relative molecular mass of silicon iodide is relatively large, the present invention selects porous carbon with a specific pore size distribution, which can effectively promote the diffusion and deposition of silicon iodide vapor with a larger relative molecular mass, so that silicon and carbon are evenly distributed in the negative electrode material, thereby effectively improving the specific capacity and first efficiency of the negative electrode material, and effectively reducing the charging volume expansion effect of the negative electrode material; finally, the addition of iodine can inhibit the decomposition of the electrolyte through its redox properties, thereby improving the safety and stability of the battery. In short, the preparation method provided by the present invention can safely and cheaply mass-produce silicon-carbon negative electrode materials with good performance under the coordinated cooperation of various process parameters.
[0042] The silicon-carbon negative electrode material provided by the present invention has high initial charge and discharge efficiency and specific capacity. In a lithium-ion battery test system, the initial reversible capacity can reach more than 1800 mA·h / g, and the initial coulombic efficiency can reach more than 90%.
[0043] The application of the silicon-carbon negative electrode material provided by the present invention can effectively increase the energy density of lithium-ion secondary batteries and effectively improve the initial charge and discharge efficiency, and has outstanding application effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 A 1000-fold scanning electron microscope image of the silicon-carbon negative electrode material provided in Example 1 of the present invention;
[0046] Figure 2 This is the first charge and discharge curve of the lithium button cell using the silicon-carbon negative electrode material obtained in Experimental Example 2 of the present invention. DETAILED DESCRIPTION
[0047] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] According to a first aspect of the present invention, there is provided a method for preparing a silicon-carbon negative electrode material, comprising the following steps:
[0049] The silicon iodide vapor is pyrolyzed in the porous carbon to deposit nano-silicon in the pore structure of the porous carbon to obtain a silicon-carbon precursor, and the silicon-carbon precursor is passivated to obtain a silicon-carbon negative electrode material;
[0050] Among them, the pore volume of porous carbon can be 0.6cm 3 / g~1.4cm 3 / g, with a typical but non-limiting pore volume of 0.6 cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1.0cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g, 1.3cm 3 / g, 1.4cm 3 / g; at the same time, the pore structure of the porous carbon includes but is not limited to pores with a diameter of 0.5nm to 3nm, pores with a diameter of 3nm to 8nm, and pores with a diameter of 8nm to 80nm.
[0051] The preparation method of silicon-carbon negative electrode material provided by the present invention adopts silicon iodide vapor as silicon source gas to deposit nano-silicon. Compared with the prior art which uses silane gas, which results in higher production cost and greater safety risk, and seriously limits the stable batch production of silicon-carbon negative electrode materials, silicon iodide has a stable structure, does not catch fire when leaked, is not flammable or explosive, can greatly improve the stability and safety of production, and can promote the industrialization progress of vapor-phase deposited silicon-carbon; in addition, iodine vapor decomposed from silicon iodide can be recycled, which can significantly reduce production costs; since silane molecules are small, they will cause faster diffusion, decomposition and deposition speed, resulting in larger nano-silicon particle size, while silicon iodide can effectively avoid the above problems due to its large molecules; at the same time, since the relative molecular mass of silicon iodide is large, the present invention selects porous carbon with a specific pore size distribution, which can effectively promote the diffusion and deposition of silicon iodide vapor with a larger relative molecular mass, so that silicon and carbon are evenly distributed in the negative electrode material; finally, the addition of iodine can inhibit the decomposition of the electrolyte through its redox properties, thereby improving the safety and stability of the battery. Therefore, the specific capacity and initial efficiency of the negative electrode material can be effectively improved, and the charging volume expansion effect of the negative electrode material can be effectively reduced.
[0052] In summary, the preparation method provided by the present invention, with the coordinated cooperation of various process parameters, can safely and low-costly mass-produce silicon-carbon negative electrode materials with good performance.
[0053] A typical method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0054] (1) Providing porous carbon with a specific pore size distribution;
[0055] (2) fully contacting the porous carbon with silicon iodide vapor, allowing the silicon iodide vapor to enter the porous structure of the porous carbon for pyrolysis, thereby causing nano-silicon particles to be deposited in the porous structure of the porous carbon, thereby obtaining a silicon-carbon precursor;
[0056] (3) Passivating the silicon-carbon precursor to obtain a silicon-carbon negative electrode material.
[0057] In a preferred embodiment, the pore volume of the porous carbon can be 0.6 cm 3 / g~1.4cm 3 / g, and may be further preferably 0.7 cm 3 / g~1.2cm 3 / g.
[0058] In a preferred embodiment, the volume proportion of pores with a diameter of 0.5nm to 3nm in the porous carbon can be 55% to 75%, for example, 55%, 60%, 65%, 70%, 75%, but not limited to this; the volume proportion of pores with a diameter of 3nm to 8nm in the porous carbon can be 10% to 20%, for example, 10%, 12%, 14%, 16%, 18%, 20%, but not limited to this; the volume proportion of pores with a diameter of 8nm to 80nm in the porous carbon can be 15% to 25%, for example, 15%, 17%, 19%, 21%, 23%, 25%, but not limited to this.
[0059] In the present invention, the specific pore volume of porous carbon and the specific pore volume ratio in different diameter ranges of 0.5nm to 3nm, 3nm to 8nm and 8nm to 80nm are more conducive to further promoting the diffusion and deposition of silicon iodide vapor with a larger relative molecular mass, making silicon and carbon more evenly distributed in the negative electrode material, which can further improve the specific capacity and initial efficiency of the negative electrode material, and further reduce the charging volume expansion effect.
[0060] In a preferred embodiment, the median particle size D50 of the porous carbon can be 1 μm to 9 μm. Its typical but non-limiting median particle size D50 is, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and may be further preferably 3 μm to 7 μm, and further preferably 4 μm to 6 μm.
[0061] In a preferred embodiment, the specific surface area of the porous carbon can be 500 m 2 / g~3000m 2 / g, with a typical but non-limiting specific surface area of, for example, 500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g、1000m 2 / g、1200m 2 / g、1500m 2 / g, 2000m 2 / g、2500m 2 / g、3000m 2 / g, and more preferably 1000m 2 / g~2500m 2 / g, more preferably 1500m 2 / g~2000m 2 / g.
[0062] In the present invention, the specific median particle size D50 and specific surface area of the porous carbon are more conducive to further evenly distributing silicon and carbon in the negative electrode material, which can further improve the specific capacity and initial efficiency of the negative electrode material, and further reduce the charging volume expansion effect.
[0063] In a preferred embodiment, the method for preparing porous carbon comprises the following steps:
[0064] (a) pre-carbonizing a carbon source material to obtain a pre-carbonized product;
[0065] (b) The pre-carbonized product of step (a) is sequentially subjected to carbonization, pulverization and activation treatment to obtain the porous carbon.
[0066] In the present invention, the pre-carbonization method includes but is not limited to at least one of solvent thermal reaction, low-temperature carbonization and spray drying; specifically, the carbon source material can be subjected to solvent thermal reaction, washed and dried to obtain a pre-carbonized product, and the solvent used includes but is not limited to at least one of water, ethanol and isopropanol; or, the carbon source material can be subjected to low-temperature carbonization and wet ball milling to obtain a pre-carbonized product; or, the carbon source material can be spray dried to obtain a pre-carbonized product.
[0067] In a preferred embodiment, the carbon source material includes but is not limited to at least one of glucose, fructose, galactose, lactose, sucrose, maltose, rice starch, mung bean starch, wheat starch, cassava starch, corn starch, cellulose and phenolic resin, which is more conducive to further improving the preparation effect of porous carbon.
[0068] In the present invention, the pre-carburized material is subjected to high-temperature carbonization, crushing and activation treatment, so as to obtain porous carbon with a median particle size D50 of 1 μm to 9 μm; wherein, the temperature of high-temperature carbonization can be 600°C to 1400°C, and its typical but non-limiting temperatures are, for example, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, and 1400°C; the time of high-temperature carbonization can be 1h to 12h, and its typical but non-limiting time is, for example, 1h, 2h, 3h, 4h, 5h, 6h, 8h, 10h, and 12h; the above-mentioned high-temperature carbonization temperature and time are more conducive to fully carbonizing the pre-carburized material.
[0069] In a preferred embodiment, the activation treatment includes but is not limited to at least one of a physical activation method and a chemical activation method; wherein the temperature of the activation treatment can be 500°C to 1100°C, and its typical but non-limiting temperatures are, for example, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, and 1100°C; the time of the activation treatment can be 1h to 12h, and its typical but non-limiting time is, for example, 1h, 2h, 3h, 4h, 5h, 6h, 8h, 10h, and 12h; the temperature and time of the above-mentioned activation treatment are more conducive to further improving the activation effect.
[0070] In the present invention, the gas used in the physical activation method includes but is not limited to at least one of water vapor, air and carbon dioxide, which is more conducive to further improving the activation effect; the chemical reagents used in the chemical activation method include but are not limited to at least one of phosphoric acid, zinc chloride, potassium hydroxide and sodium hydroxide, which is more conducive to further improving the activation effect.
[0071] In a preferred embodiment, the method for preparing silicon iodide vapor comprises the following steps:
[0072] High-temperature iodine vapor is introduced into silicon particles for reaction to obtain silicon iodide vapor;
[0073] Among them, silicon particles include but are not limited to at least one of metallic silicon, high-purity silicon and ultra-pure silicon; the size (particle diameter) of silicon particles can be 0.1mm~500mm, for example, it can be 0.1mm, 1mm, 5mm, 10mm, 20mm, 40mm, 80mm, 160mm, 320mm, 500mm, but not limited to this; the reaction temperature can be 700℃~900℃, and its typical but non-limiting reaction temperature is, for example, 700℃, 750℃, 800℃, 850℃, 900℃.
[0074] In the present invention, the silicon element obtained after the silicon iodide is thermally decomposed into nano-silicon particles, and the median particle size D50 of the nano-silicon particles may be less than 20 nm.
[0075] The present invention adopts silicon iodide vapor as silicon source gas and prepares silicon carbon precursor by vapor deposition. The equipment adopted for vapor deposition includes but is not limited to at least one of a chemical vapor deposition furnace and a fluidized bed. The temperature of vapor deposition can be 600°C to 1200°C, and its typical but non-limiting temperatures are, for example, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, and 1200°C. The time of vapor deposition can be 1h to 24h, and its typical but non-limiting time is, for example, 1h, 3h, 5h, 7h, 9h, 12h, 14h, 16h, 18h, 20h, 22h, and 24h.
[0076] In the present invention, vapor deposition can be performed in an inert gas.
[0077] The vapor deposition method and process parameters selected by the present invention are safer, convenient for large-scale production, and can further ensure the preparation quality of the silicon-carbon precursor.
[0078] In a preferred embodiment, the passivation treatment method of the silicon-carbon precursor includes but is not limited to gas phase passivation treatment, and the equipment used for the gas phase passivation treatment includes but is not limited to at least one of a chemical vapor deposition furnace and a fluidized bed.
[0079] In a preferred embodiment, the gas used for the gas phase passivation treatment includes but is not limited to at least one of methane, ethane, propane, butane, ethylene, propylene, butene, 1,3-butadiene, acetylene, methylacetylene, cyclopropane and methyl chloride, which is more conducive to further improving the passivation effect of the silicon-carbon precursor.
[0080] In a preferred embodiment, the temperature of the vapor phase passivation treatment can be 400°C to 800°C, and typical but non-limiting temperatures are, for example, 400°C, 500°C, 600°C, 700°C, and 800°C. The time of the vapor phase passivation treatment can be 1h to 24h, and typical but non-limiting times are, for example, 1h, 3h, 5h, 7h, 9h, 12h, 14h, 16h, 18h, 20h, 22h, and 24h, which is more conducive to further improving the passivation effect of the silicon-carbon precursor.
[0081] In a preferred embodiment, the gas phase passivation treatment process also includes a step of passivation treatment using air or oxygen, and the treatment temperature can be 10°C to 100°C, for example, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, but not limited to this, and the treatment time can be 1h to 24h, for example, 1h, 3h, 5h, 7h, 9h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, but not limited to this.
[0082] In the present invention, the passivation treatment can be carried out in an inert gas, and the passivation layer formed after the passivation treatment can account for 0.1% to 5% of the mass of the silicon-carbon negative electrode material, for example, it can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, but not limited to this.
[0083] The passivation treatment method and process parameters of the present invention are more conducive to further improving the treatment effect of the silicon-carbon precursor, thereby obtaining a silicon-carbon negative electrode material with better quality.
[0084] According to a second aspect of the present invention, there is provided a silicon-carbon negative electrode material prepared by any of the preparation methods described above, wherein the negative electrode material mainly consists of porous carbon and nano-silicon particles uniformly distributed therein.
[0085] In the present invention, the structure of the silicon-carbon negative electrode material can be expressed as Si / C m , wherein 0.25≤m≤4, and m can be, for example, 0.25, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, or 4, but is not limited thereto.
[0086] The silicon-carbon negative electrode material provided by the present invention has nano-silicon particles that can be relatively evenly distributed in the porous carbon, has high initial charge and discharge efficiency and specific capacity, and in a lithium-ion battery test system, the initial reversible capacity can reach more than 1800 mA·h / g, and the initial coulombic efficiency can reach more than 90%.
[0087] In a preferred embodiment, the median particle size D50 of the silicon-carbon negative electrode material can be 2μm to 10μm, and its typical but non-limiting median particle size D50 is, for example, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, and can be further preferably 3μm to 7μm, and further preferably 5μm to 6μm.
[0088] In a preferred embodiment, the specific surface area of the silicon-carbon negative electrode material can be 0.5 m 2 / g~15m 2 / g, with a typical but non-limiting specific surface area of, for example, 0.5 m 2 / g, 1.0m 2 / g, 2.0m 2 / g, 3.0m 2 / g, 4.0m 2 / g, 5.0m 2 / g, 6.0m 2 / g, 7.0m 2 / g, 8.0m 2 / g, 9.0m 2 / g, 10m 2 / g, 11.0m 2 / g, 12.0m 2 / g, 13.0m 2 / g, 14.0m 2 / g, 15m 2 / g, and may be further preferably 1m 2 / g~8m 2 / g, more preferably 2m 2 / g~4m 2 / g.
[0089] The median particle size D50 and specific surface area selected for the silicon-carbon negative electrode material of the present invention are more conducive to further evenly distributing silicon and carbon in the negative electrode material, which can further improve the specific capacity and initial efficiency of the negative electrode material, and further reduce the charging volume expansion effect.
[0090] In a preferred embodiment, the mass content of iodine in the silicon-carbon negative electrode material can be 0.01% to 0.20%, and its typical but non-limiting mass content is, for example, 0.01%, 0.05%, 0.10%, 0.15%, 0.20%, and can be further preferably 0.05% to 0.20%.
[0091] In a preferred embodiment, the nano-silicon particles distributed in the porous carbon may be amorphous silicon, and the average particle size D50 thereof may be less than 20 nm, for example, 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, but not limited thereto.
[0092] In a preferred embodiment, the content of nano silicon particles in the silicon-carbon negative electrode material can be 20wt% to 80wt%, and its typical but non-limiting content is, for example, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, and can be further preferably 30wt% to 60wt%, and further preferably 40wt% to 50wt%.
[0093] In the present invention, the selected type of nano silicon particles and their average particle size, as well as their mass proportion in the negative electrode material, are more conducive to further improving the initial efficiency and specific capacity of the negative electrode material, and are more conducive to further making the negative electrode material have a lower charging volume expansion effect.
[0094] According to a third aspect of the present invention, there is provided a use of the silicon-carbon negative electrode material described in any one of the above items in a lithium-ion secondary battery.
[0095] The application of the silicon-carbon negative electrode material provided by the present invention can effectively increase the energy density of lithium-ion secondary batteries and effectively improve the initial charge and discharge efficiency, and has outstanding application effects.
[0096] In a preferred embodiment, the secondary battery composed of the silicon-carbon negative electrode material and metallic lithium as the counter electrode has a negative electrode capacity of ≥1800mA·h / g and a first efficiency of ≥90% when discharged at a constant current to 0.005V and then charged at a constant current to a voltage of 1.5V.
[0097] In the present invention, a silicon-carbon negative electrode material and a secondary battery composed of metallic lithium as a counter electrode are subjected to charge and discharge tests. The discharge process is the reaction of lithium ions entering the negative electrode material, and the charging process is the reaction of lithium ions escaping from the negative electrode material. The capacity Q of the charging process is differentiated from the voltage V of the negative electrode material, and the obtained differential value dQ / dV is plotted against the voltage V. The negative electrode has a steamed bun peak in the voltage range of 0.4V to 0.5V.
[0098] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0099] Example 1
[0100] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0101] S1: Mix rice starch and phosphoric acid for low-temperature carbonization at 300°C, add the mixture into a ball mill and mill for 12 hours to obtain a pre-carbonized product;
[0102] S2: The pre-carbide is subjected to high temperature carbonization at 1200°C for 4 hours in a box-type atmosphere furnace, and high temperature carbide is obtained after air flow pulverization;
[0103] S3: The high-temperature carbide is introduced into carbon dioxide in a rotary furnace for high-temperature activation at 900°C for 5 hours to obtain a porous carbon material, the physical and chemical index parameters of which are shown in Table 1;
[0104] S4: The porous carbon material and silicon iodide vapor were pyrolyzed at 1000°C for 4 h in a CVD furnace to deposit nano-silicon in the pore structure of the porous carbon to obtain a silicon-carbon precursor. Then, methane was introduced to passivate the silicon-carbon precursor for 1 h to obtain a silicon-carbon negative electrode material. The physical and chemical index parameters are shown in Table 2, and the 1000x scanning electron microscope image is shown in Figure 1 .
[0105] Example 2
[0106] The difference between this embodiment and embodiment 1 is that in step S1, rice starch is replaced with cassava starch in this embodiment; in step S4, methane is replaced with ethylene in this embodiment, thereby passivating the silicon-carbon precursor;
[0107] The remaining steps and their parameters are the same as those in Example 1 to obtain porous carbon materials and silicon-carbon negative electrode materials.
[0108] The physical and chemical index parameters of the porous carbon material of this embodiment are shown in Table 1, and the physical and chemical index parameters of the silicon-carbon negative electrode material are shown in Table 2.
[0109] Example 3
[0110] The difference between this embodiment and embodiment 1 is that in step S1, phosphoric acid is replaced by sodium hydroxide solution in this embodiment; in step S3, carbon dioxide is replaced by water vapor in this embodiment for activation;
[0111] The remaining steps and their parameters are the same as those in Example 1 to obtain porous carbon materials and silicon-carbon negative electrode materials.
[0112] The physical and chemical index parameters of the porous carbon material of this embodiment are shown in Table 1, and the physical and chemical index parameters of the silicon-carbon negative electrode material are shown in Table 2.
[0113] Example 4
[0114] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0115] S1: Mix glucose and pure water in an autoclave and perform low-temperature carbonization at 220°C for 4 hours, then wash and dry to obtain a pre-carbonized product;
[0116] S2: The pre-carbide is subjected to high temperature carbonization at 1200°C for 4 hours in a box-type atmosphere furnace, and high temperature carbide is obtained after air flow pulverization;
[0117] S3: The pre-carbonized material is mixed evenly with sodium hydroxide and then carbonized at 1150°C for 2 h in a box-type atmosphere furnace, and then pulverized by air flow to obtain a porous carbon material, the physical and chemical index parameters of which are shown in Table 1;
[0118] S4: The porous carbon material and silicon iodide vapor were pyrolyzed at 950°C in a CVD furnace for 4 h to deposit nanosilicon in the pore structure of the porous carbon to obtain a silicon-carbon precursor. Acetylene was then introduced to passivate the silicon-carbon precursor for 1.5 h to obtain a silicon-carbon negative electrode material. The physical and chemical index parameters are shown in Table 2.
[0119] Example 5
[0120] The difference between this embodiment and embodiment 4 is that in step S1, glucose is replaced by phenolic resin and pure water is replaced by ethanol.
[0121] The remaining steps and their parameters are the same as those in Example 4 to obtain porous carbon materials and silicon-carbon negative electrode materials.
[0122] The physical and chemical index parameters of the porous carbon material of this embodiment are shown in Table 1, and the physical and chemical index parameters of the silicon-carbon negative electrode material are shown in Table 2.
[0123] Example 6
[0124] The difference between this embodiment and embodiment 4 is that in step S1, glucose is replaced with sucrose in this embodiment; in step S4, the thermal decomposition time of silicon iodide is changed to 4.5h;
[0125] The remaining steps and their parameters are the same as those in Example 4 to obtain porous carbon materials and silicon-carbon negative electrode materials.
[0126] The physical and chemical index parameters of the porous carbon material of this embodiment are shown in Table 1, and the physical and chemical index parameters of the silicon-carbon negative electrode material are shown in Table 2.
[0127] Comparative Example 1
[0128] The difference between this comparative example and Example 1 is that in step S4, this comparative example uses monosilane to replace silicon iodide vapor to perform thermal decomposition;
[0129] The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material, and its physical and chemical index parameters are shown in Table 2.
[0130] Compared with Example 1, the defects of this comparative example are that the particle size and expansion of nano-silicon are slightly larger, and monosilane is flammable and explosive, posing a great safety risk.
[0131] Comparative Example 2
[0132] The difference between this comparative example and Example 1 is that in step S4, this comparative example uses disilane to replace silicon iodide vapor to perform thermal decomposition;
[0133] The remaining steps and their parameters are as in Example 1 to obtain a silicon-carbon negative electrode material, and its physical and chemical index parameters are shown in Table 2.
[0134] Test Example 1
[0135] The physical and chemical parameters of the porous carbon materials obtained in Examples 1-6 are shown in Table 1.
[0136] The particle size range (μm) of the material was tested by Dandong Better Laser Particle Size Analyzer BT-9300ST; the phase analysis of the material was performed by XRD diffractometer (Holland Panalytical X'PERT PRO MPD); the specific surface area (m 2 / g); the pore size distribution of the material was tested using American Quantachrome Autosorb IQ3.
[0137] Table 1
[0138]
[0139] It can be seen from Table 1 that in Examples 1-6, the carbon source type, different preparation and activation methods, etc. all affect the physical and chemical indicators of the porous carbon, such as particle morphology, pore size distribution, particle size and specific surface area, to a certain extent; the porous carbon obtained in Examples 1-6 has a higher specific surface area, and a larger pore volume of 3nm-8nm and 8nm-80nm, which is mainly affected by the activation method and the carbon source type.
[0140] The physical and chemical index parameters of the silicon-carbon negative electrode materials obtained in Examples 1-6 and Comparative Examples 1-2 are shown in Table 2.
[0141] Table 2
[0142]
[0143] It can be seen from Table 2 that in Examples 1-6 and Comparative Examples 1-2, the particle size and specific surface area of the silicon-carbon negative electrode materials obtained by different carbon sources and different preparation methods have great differences. The difference in particle size mainly comes from the preparation and treatment of the porous carbon material, and the difference in specific surface area is determined by the porous carbon, nano-silicon deposition process and passivation treatment.
[0144] Test Example 2
[0145] Lithium button cell battery test:
[0146] The first reversible capacity and first efficiency of the silicon-carbon negative electrode materials obtained in Examples 1-6 and Comparative Examples 1-2 were tested as follows:
[0147] Silicon-carbon negative electrode material, conductive carbon black and binder are mixed in pure water at a mass ratio of 94.5:1.5:4, homogenized, and the solid content is controlled to be 48wt%, coated on a copper foil current collector, vacuum-baked at 100°C to 110°C for 8h, pressed and formed, and then punched to prepare a negative electrode sheet;
[0148] The button half-cell was assembled in an argon-filled glove box. The counter electrode was a metal lithium sheet, the separator was PE, and the electrolyte was 1 mol / L LiPF 6 EC / DMC (Vol 1:1);
[0149] The button cell was charged and discharged. The test process was 0.2C DC to 0V, 0.05C DC to 0V, 0V CV 50μA, 0.01C DC to 0V, 0V CV 20μA, Rest 10min, 0.2C CC to 2V.
[0150] The first reversible capacity and efficiency of the negative electrode material were measured. The testing equipment for the button battery was the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.
[0151] Expansion rate test of negative electrode material S600:
[0152] The silicon-carbon negative electrode materials obtained in Examples 1-6 and Comparative Examples 1-2 were tested for their first reversible capacity by the above-mentioned charge-discharge test method, and then a certain amount of the same graphite negative electrode was mixed according to the calculation, and the negative electrode materials were mixed to 600±5 mA·h / g, abbreviated as S600;
[0153] S600 mixed material, conductive carbon black and binder (mass ratio 92:2:6) were homogenized in pure water to control the solid content to 48%, and then coated on a current collector with a copper foil as the substrate, and then vacuum baked at 80°C to 90°C for 8h, pressed by a roller press, and then sliced by a slicing device to prepare a negative electrode sheet; the thickness of the negative electrode sheet was measured with a micrometer, recorded as T1, and the thickness of the substrate was measured as T2, and the data were recorded;
[0154] The button half-cell was assembled in a glove box filled with argon. The counter electrode was a metal lithium sheet, the diaphragm was made of PE, and the electrolyte was 1 mol / L LiPF 6 EC / DMC (Vol 1:1); charge and discharge test of button cell, test process 0.1CDC to 0.005V, 0.05C DC to 0.005V, 0.02C DC to 0.005V, Rest 10min, 0.1C CC to1.5V, 0.1C DC to 0.005V, 0.05C DC to 0.005V, 0.02C DC to 0.005V; measure the first reversible capacity and efficiency of negative electrode material;
[0155] The battery was disassembled and the thickness of the negative electrode material obtained was detected and recorded as T3. The first full-charge expansion data of the negative electrode material was calculated according to the formula F=(T3-T1) / (T1-T2), where F is the first full-charge expansion rate.
[0156] The button cell testing equipment is the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.; the slicing equipment is the MSK-T10 button half-cell slicing equipment of Kejing; the micrometer detection equipment is the Japanese Mitutoyo 293-100-10; and the rolling equipment is the MSK-HRP-05 button half-cell slicing equipment of Kejing.
[0157] The above test results are shown in Table 3, and the first charge and discharge curve of the lithium button battery of the silicon-carbon negative electrode material of Example 1 is shown in Figure 2 .
[0158] Table 3
[0159]
[0160] As can be seen from Table 3, the silicon-carbon negative electrode materials obtained in Examples 1-6 have higher specific capacity and first efficiency. In the lithium-ion battery test system, the first reversible capacity can reach more than 1800 mA·h / g, and the first coulombic efficiency is more than 90%; the changes in the type of carbon source and the preparation and activation method in Examples 1-6 can greatly affect the first efficiency and S600 first expansion rate of the negative electrode material. The porous carbon with a large specific surface area and a high proportion of macropores in Examples 1-6 can allow nano-silicon to be deposited inside the pores of the porous carbon. At the same time, after passivation treatment, the surface nano-silicon is isolated from direct contact with the electrolyte, which helps to reduce the occurrence of side reactions during charging and avoid repeated formation of SEI, thereby reducing the volume expansion change of the negative electrode material during the lithium insertion process; in Example 6, the thermal decomposition time of silicon iodide vapor is increased, the silicon content is increased, and therefore the capacity is increased. At the same time, the nano-silicon particle size is also larger, and the corresponding first expansion rate is also larger.
[0161] The first effect of the silicon-carbon negative electrode material of comparative example 1-2 is slightly lower, and the expansion and nano-silicon particle size are larger. The reason is that silane is used as the silicon source gas, the deposition speed is too fast, the generated nano-silicon particle size is slightly larger, and there is no beneficial effect of iodine element in inhibiting the decomposition of the electrolyte.
[0162] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a silicon-carbon negative electrode material, characterized in that: The following steps are involved: The silicon iodide vapor is pyrolyzed in the porous carbon to deposit nano-silicon in the pore structure of the porous carbon to obtain a silicon-carbon precursor, and the silicon-carbon precursor is passivated to obtain the silicon-carbon negative electrode material; The pore volume of the porous carbon is 0.6 cm 3 / g~1.4cm 3 / g between; The pore structure of the porous carbon includes pores with a diameter of 0.5 nm to 3 nm, pores with a diameter of 3 nm to 8 nm, and pores with a diameter of 8 nm to 80 nm.
2. The preparation method according to claim 1, characterized in that: The volume proportion of pores with a diameter of 0.5 nm to 3 nm in the porous carbon is 55% to 75%; The volume proportion of pores with a diameter of 3 nm to 8 nm in the porous carbon is 10% to 20%; The volume proportion of pores with a diameter of 8 nm to 80 nm in the porous carbon is 15% to 25%.
3. The preparation method according to claim 1, characterized in that: The median particle size D50 of the porous carbon is 1 μm to 9 μm; The specific surface area of the porous carbon is 500 m 2 / g~3000m 2 / g.
4. The preparation method according to any one of claims 1 to 3, characterized in that The method for preparing the porous carbon comprises the following steps: (a) pre-carbonizing a carbon source material to obtain a pre-carbonized product; (b) the pre-carbonized product is subjected to carbonization, pulverization and activation treatment to obtain the porous carbon; The carbon source material comprises at least one of glucose, fructose, galactose, lactose, sucrose, maltose, rice starch, mung bean starch, wheat starch, cassava starch, corn starch, cellulose and phenolic resin; The pre-carbonization method comprises at least one of solvent thermal reaction, low temperature carbonization and spray drying; The activation treatment includes at least one of a physical activation method and a chemical activation method; The gas used in the physical activation method includes at least one of water vapor, air and carbon dioxide; The chemical reagents used in the chemical activation method include at least one of phosphoric acid, zinc chloride, potassium hydroxide and sodium hydroxide.
5. The preparation method according to any one of claims 1 to 3, characterized in that: Preparation method of silicon iodide vapor The following steps are involved: Iodine vapor is introduced into silicon particles for reaction to obtain silicon iodide vapor; The silicon particles include at least one of metallic silicon, high-purity silicon and ultra-pure silicon; The particle size of the silicon particles is between 0.1 mm and 500 mm.
6. A silicon-carbon negative electrode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 5.
7. The silicon-carbon negative electrode material according to claim 6, characterized in that: The general structural formula of the silicon-carbon negative electrode material is Si / C m , where 0.25≤m≤4; The mass content of iodine in the silicon-carbon negative electrode material is 0.01% to 0.20%; The median particle size D50 of the silicon-carbon negative electrode material is 2 μm to 10 μm; The specific surface area of the silicon-carbon negative electrode material is 0.5 m 2 / g~15m 2 / g.
8. The silicon-carbon negative electrode material according to claim 6 or 7, characterized in that: The nano-silicon content in the silicon-carbon negative electrode material is 20wt% to 80wt%; The average particle size D50 of the nano-silicon is less than 20 nm.
9. Use of the silicon-carbon negative electrode material according to any one of claims 6 to 8 in a lithium-ion secondary battery.
10. The use according to claim 9, characterized in that: When the battery is discharged to 0.005V at a constant current and then charged to 1.5V at a constant current, the negative electrode capacity of the lithium ion secondary battery is ≥1800mA·h / g and the initial efficiency is ≥90%.